2017
DOI: 10.1016/j.jad.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the relationship between anxiety, anhedonia, and depression

Abstract: Introduction Anxiety and depression are often comorbid conditions, but there is uncertainty as to how this comorbidity develops. Thus, in three studies, we attempted to discern whether anhedonia may be a key linking factor between anxiety and depression. Methods Three studies asked participants about their symptoms of anxiety and depression: in Study 1, 109 participants completed measures of anxiety, depression, activity avoidance, and perceived enjoyability and importance of avoided activities; in Study 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 47 publications
3
51
0
3
Order By: Relevance
“…Supporting this model is evidence that altered structure and function in the putamen and caudate are associated with symptoms of anhedonia and poorer impulse control in both non-clinical and clinical samples (Martinot et al ., 2001 ; Dalley and Roiser, 2015 ; Der-Avakian and Markou, 2016 ). For example several researchers have found that anhedonia is in association with SI independently of depression symptoms (Winer et al ., 2014 , 2017 ; Auerbach et al ., 2015 ; Ducasse et al ., 2017 ). Recently, Auerbach and colleagues reported that reduced putamen GMV in female adolescents prospectively predicted severity of anhedonia 3 months later (Auerbach et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this model is evidence that altered structure and function in the putamen and caudate are associated with symptoms of anhedonia and poorer impulse control in both non-clinical and clinical samples (Martinot et al ., 2001 ; Dalley and Roiser, 2015 ; Der-Avakian and Markou, 2016 ). For example several researchers have found that anhedonia is in association with SI independently of depression symptoms (Winer et al ., 2014 , 2017 ; Auerbach et al ., 2015 ; Ducasse et al ., 2017 ). Recently, Auerbach and colleagues reported that reduced putamen GMV in female adolescents prospectively predicted severity of anhedonia 3 months later (Auerbach et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anticipatory pleasure was found to be uncorrelated with the severity of anxiety symptoms in this study. It is possible that the reported correlation between anhedonia and anxiety symptoms severity may mainly lie in consummatory pleasure (Winer et al, ). Our finding is also in line with previous studies reporting that individuals with anxiety symptoms would anticipate more negative emotions but a similar level of positive emotion compared with healthy controls (Hoerger, Quirk, Chapman, & Duberstein, ; Wenze, Gunthert, Ahrens, & Taylor Bos, ).…”
Section: Discussionmentioning
confidence: 99%
“…Anhedonia is characterized by a reduced ability to experience pleasure and is a core symptom of schizophrenia (Strauss & Cohen, ) and depression (Yang et al, ). It is also reported in autism spectrum disorders (ASD; Chevallier, Grezes, Molesworth, Berthoz, & Happe, ; Novacek, Gooding, & Pflum, ) and obsessive–compulsive disorder (OCD; Abramovitch, Pizzagalli, Reuman, & Wilhelm, ), and is associated with anxiety symptoms (Winer et al, ).…”
mentioning
confidence: 99%
“…De plus, certaines études (par exemple, Khazanov & Ruscio, 2016 ;Kotov et al, 2010) remettent en question le caractère spécifique au trouble dépressif eu égard au manque d'affects positifs. En effet, bien que la méta-analyse de Khazanov et Ruscio (2016) En effet, bien qu'une série d'études (par exemple, Starr & Davila, 2012;Winer et al, 2017) suggère que l'anxiété précéderait la dépression, selon Klenk et collègues (2011), tant l'anxiété que la dépression pourraient jouer un rôle dans le déclenchement du trouble anxio-dépressif. Par ailleurs, ce modèle souligne l'importance des processus attentionnels, déjà largement développés dans la littérature (par exemple, Richards et al, 2014;Wermes et al, 2018), en soutenant le rôle central de l'hypervigilance dans la cascade d'éléments intervenant lors du déclenchement du trouble.…”
Section: Modèle Tripartite De Clark and Watson (1991)unclassified
“…Alors que certaines approches considèrent que l'anxiété précéderait la dépression (par exemple, Klenk et al, 2011;Price et al, 2016;Winer et al, 2017), d'autres considèrent que la dépression précèderait l'anxiété (par exemple, Klenk et al, 2011), ou que ces deux troubles apparaitraient simultanément (Cramer et al, 2010). A la lumière de la littérature actuelle, la question de la temporalité de la comorbidité est loin d'être résolue.…”
Section: Perspectives Et Conclusionunclassified